The Effects of Target Location Upon Throwing Velocity and Accuracy in Experienced Female Handball Players - van den Tillaar, Roland (Frontiers in Psychology, 2020)
The purpose of this study was to investigate the effect on throwing performance (velocity and accuracy) of experienced female handball players when throwing at four different targets in a handball goal. Thirteen experienced female handball players (age 18.2±1.7 years, height 1.7±0.10 m, mass 68.1±19.6 kg, training experience 9.5±3.7 years) performed 10 throws from a 7 m distance at each corner of the handball goal with maximal effort. Maximal ball velocity was recorded with a radar gun, together with mean radial error, centroid error and bivariate variable error, as measurements of accuracy. The main findings were that the ball velocity was higher when throwing at targets at the ipsilateral side, compared with the contralateral side, while throwing consistency (bivariate variable error) decreased when throwing at the contralateral side upper corner. No velocity-accuracy trade off was found between the four targets. Based upon the findings it is suggested that players throw to the (upper) ipsilateral side of the goal when performing a penalty throw, dependent on the goalkeepers’ position, since the ball velocity is the highest here, without losing accuracy. This gives the goalkeeper less time to react and stop the ball, thereby giving the player the highest chance of scoring.